2005
DOI: 10.4141/s04-078
|View full text |Cite
|
Sign up to set email alerts
|

The role of crop rotations in determining soil structure and crop growth conditions

Abstract: . 2005. The role of crop rotations in determining soil structure and crop growth conditions. Can. J. Soil Sci. 85: 557-577. Increasing concern about the need to provide high-quality food with minimum environmental impact has led to a new interest in crop rotations as a tool to maintain sustainable crop production. We review the role of rotations in the development and preservation of soil structure. After first introducing the types of rotations in current practice and their impact on yield, we assess how soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(140 citation statements)
references
References 181 publications
2
134
0
4
Order By: Relevance
“…The role of crop rotations in determining soil structure and crop growth conditions has been recognised as being of prime importance for sustainable crop production (Ball et al, 2005). In organic cropping, the management of grass swards is of particular interest for the maintenance of soil structure (Ball et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The role of crop rotations in determining soil structure and crop growth conditions has been recognised as being of prime importance for sustainable crop production (Ball et al, 2005). In organic cropping, the management of grass swards is of particular interest for the maintenance of soil structure (Ball et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Materechera et al (1992) also observed a lower proportion of large aggregates in agricultural clay soils cultivated with Lolium multiflorum compared to Triticum spp and Pisum sativum, attributing this result to the greater root length of Lolium multiflorum. The root system of grasses can lead to the change of more compact aggregates into less compact aggregates (Portella et al, 2012) by breaking the aggregates and then reshaping them (Terpstra, 1990) or by stresses generated in the soil-root interface during water extraction, which cause cracks in the soil (Ball et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Soil structure can also influence the rooting pattern by inhibiting the downward growth of roots into horizons with a greater bulk density (such as solonetzic Bnt horizons) or by causing roots to cluster within certain zones in the soil. These patterns can negatively impact the ability of roots to take up both moisture and nutrients, necessarily reducing yield (Ball et al 2005). …”
Section: Texture and Landform Considerationsmentioning
confidence: 99%
“…It can reduce plant-available water by twice as much as continuous cropping alone, and by more than four times as much as a crop-fallow system (Eilers et al 1995). Compared with continuous annual crops and pastures, alfalfa provides a threefold increase in the number of large pores (2 mm) in the subsoil and these pores persist for 2 yr or more after the alfalfa has been removed, improving infiltration (Ball et al 2005). It is also a high-water use plant, and with its deep roots, serves to draw down the water table to a much greater depth than annual crops, reducing the risk of secondary salinity associated with a shallow water table (Ridley et al 2001).…”
Section: Crop Selection and Rotationsmentioning
confidence: 99%
See 1 more Smart Citation